جەنگى دەروونى لە مێژووى ئیسلامدا "لە سەرەتاى ئیسلامەوە تا سەردەمى مەغۆلەکان" - زەینەل, ئاراس فەریق (Sulaimani Journal for Humanities, 2007)
Psychological war takes up an important Posit ion at the present time ware than any other era. currently it is regarded the most significant subject mainly from social psychology and military psychology in any historical period of an army, party , nation or state to stand against enemies . Although it was used in ancient times and produced many styles. The great development which offected each staye may be the cause of inventing new styles for this war in which it is not different from its existing shapes only in mains and application . Its main aim is to affect the sense of enemies and to crush their mental power. Psychological war is the more ancient truth and it is existed in the ancient cultures and it is existed since the foundation of human conflict its usage returns returns to the ancient cultures . There were various primitive styles by the groups, nations and states in addition to the historical evidence and its practical applications in which the sharp – witted and skilful rules and leaders try to use it widely.